2005
DOI: 10.1177/1077546305048325
|View full text |Cite
|
Sign up to set email alerts
|

Optimization Analysis of Impact Viscous Damper for Controlling Self-Excited Vibrations

Abstract: We present a numerical study for the suppression of self-excited vibrations represented by a Rayleigh oscillator using an impact viscous damper. A systematic approach based on a univariate search optimization method is used to determine the best design parameters for suppressing self-excited vibrations. The suggested system is found to be effective in suppressing this type of vibration. Optimum parameters for complete quenching of such vibrations are obtained. We investigate quasi-static as well as dynamic var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The hyper-surface Σ α defines the transition from Γ − to Γ + , i.e., when the mass initiates the contact with the support, Σ α = x ∈ R 2 h α (θ,θ) = 0 and h β (θ,θ) 0 . (11) Surface Σ β defines the transition from Γ + to Γ − as the contact is lost when the impact force vanishes:…”
Section: Mathematical Modeling and Comparison Between Numerical Simulmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyper-surface Σ α defines the transition from Γ − to Γ + , i.e., when the mass initiates the contact with the support, Σ α = x ∈ R 2 h α (θ,θ) = 0 and h β (θ,θ) 0 . (11) Surface Σ β defines the transition from Γ + to Γ − as the contact is lost when the impact force vanishes:…”
Section: Mathematical Modeling and Comparison Between Numerical Simulmentioning
confidence: 99%
“…The study of vibro-impact systems has been the aim of several researches, from the application of a percussive action in rotary drilling for improved performance [5][6][7], to ultrasonic drilling [8][9][10], impact dampers [11,12] and vibro-safe percussion machines [13].…”
mentioning
confidence: 99%
“…The trial result revealed that the proposed three-dimensional isolation fl oor can successfully shield the computer system in a nuclear power plant from external vibration. Asfar and Akour (2005) utilized a viscous damper to suppress self-excited vibrations. Viscous dampers have also been applied to 3D irregularly framed structures with the peripheral drift constrained.…”
Section: Introductionmentioning
confidence: 99%
“…The study of vibro-impact systems has been the aim of several researches, from the application of a percussive action in rotary drilling for improved performance [5][6][7], to ultrasonic drilling [8][9][10], impact dampers [11,12] and vibro-safe percussion machines [13]. In general, experimental contributions have been rather limited.…”
Section: Introductionmentioning
confidence: 99%